A comparative study of concentrated plasticity models in dynamic analysis of building structures. - Dides, Maurice A.
Concentrated plasticity (CP) models are frequently used in static and dynamic building analysis and have been implemented in available commercial software. This investigation deals with three different CP-models, a simplified macroelement model (SEM) for a complete building story, a frame element with elasto-plastic interaction hinges (PH), and a frame element with fiber hinges (FB). The objectives of this work are to evaluate the quality of the earthquake responses predicted by these models and to identify important aspects of their implementation and limitations for their use in dynamic analysis. The three elements are tested in a single story asymmetric plan building and in a three story steel building. Results show that base shear and global response values are usually computed with better accuracy than interstory deformations and local responses. Besides, the main limitation of elasto plastic CP models is to control the displacement offsets that result from perfect elasto plastic behavior. On the other hand, calibration of the SEM model shows that global responses in steel structures may be computed within 20 percent error in the mean at a computational cost two orders of magnitude smaller than that of the other CP elements considered. However, the three element models considered lead to increasing levels of accuracy in the dynamic response and their use depends on the refinement of the analysis performed.
Keywords: Inelastic dynamic analysis; Pushover; Inelastic frame elements; Hinge elements; Fiber elements; Calibration of inelastic models; Concentrated plasticity